(untitled) (Mūzikas akadēmijas raksti, 2024)
Opinions on national culture expressed by its very own representatives, as well as observers, will never be identical. Their comparison is engaging and a theme worthy of research, as it can answer the question: in national culture, what is interesting and striking not just locally, but also when looking at the broader context? The analysis of this question can be very extensive. The goal of this paper is to reveal a single aspect of such analysis: to compare diverse opinions on the creative work of Jāzeps Vītols expressed in the Riga German and Russian press during the time of this composer’s greatest activity – from the 1880s to the 1930s. During the first period of Vītols’ work – the end of the 19th century and the beginning of the 20th century, one of the main national awakening inspired tendencies in his, as well as other Latvian contemporaries’ creative work, is the expression of national motifs. With Latvian audiences, as well as music critics, this theme usually generates an enthusiastic response, however, the non-Latvian press sees it in a more contradictory light. The triumphant progress of National Romanticism in Europe is viewed by the majority of Riga’s German music critics if not negatively, then at least as something debateable. This is confirmed by, for example, reviews written by Moritz Rudolph (Rigaer Tageblatt, July 21, 1889) and Hans Schmidt (Rigasche Rundschau, September 4, 1906; November 28, 1911) on folklore-inspired works by Vītols.